Analisis Laporan Keuangan PT Gudang Garam Tbk - Ega Ari Lesmana; Arditya Devrian Albar; Sri Hermuningsih (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract: This study aims to evaluate the financial performance of PT Gudang Garam Tbk for the 2024–2025 period using a descriptive quantitative method, focusing on the analysis of liquidity, activity, solvency, and profitability ratios based on industry standards as defined by Kasmir (2019). The results indicate that the company demonstrates a high level of resilience, characterized by a very healthy liquidity position with a current ratio of 3.68 times and a highly effective debt collection policy averaging 8 days. Although inventory turnover requires 151 days due to the technical characteristics of the tobacco industry, the company successfully minimized financial risk significantly, with the Debt-to-Equity Ratio (DER) decreasing to 20.27% and the Debt-to-Asset Ratio (DAR) to 16.85%. Regarding profitability, despite a 9.4% contraction in sales volume, aggressive operational cost efficiency strategies managed to drive a 59% surge in net profit, subsequently increasing the Return on Assets (ROA) to 2.07% and Return on Equity (ROE) to 2.49%. The study concludes that the management has successfully optimized assets and strengthened its capital structure independently; therefore, it is recommended to pursue strategic investment diversification to leverage the strong cash position for future business sustainability.